2022
DOI: 10.31331/medivesveteran.v6i1.1901
|View full text |Cite
|
Sign up to set email alerts
|

Improving Student’s Critical Thinking Skill in Mathematics Through Geogebra-Based Flipped Learning During Pandemi Covid-19: an Experimental Study

Abstract: w

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Previous studies have investigated the integration of Flipped Learning model and GeoGebra, such as; (1) Nuraeni et al (2021), who developed a learning tool on the flipped learning model assisted by GeoGebra to improve the mathematical representative skills of secondary school students in Indonesia, (2) Ishartono et al (2022) who studied the integration of GeoGebra into Flipped Learning model to improve students' self-regulated learning, and (3) Andriani et al (2022) who integrated Flipped Learning and GeoGebra to improve students' critical thinking skills during online learning. However, there is a lacuna in studies which examine how the integration of GeoGebra and Flipped Learning increases students' independence in learning mathematics during the Covid-19 pandemic.…”
Section: Significance Of the Studymentioning
confidence: 99%
“…Previous studies have investigated the integration of Flipped Learning model and GeoGebra, such as; (1) Nuraeni et al (2021), who developed a learning tool on the flipped learning model assisted by GeoGebra to improve the mathematical representative skills of secondary school students in Indonesia, (2) Ishartono et al (2022) who studied the integration of GeoGebra into Flipped Learning model to improve students' self-regulated learning, and (3) Andriani et al (2022) who integrated Flipped Learning and GeoGebra to improve students' critical thinking skills during online learning. However, there is a lacuna in studies which examine how the integration of GeoGebra and Flipped Learning increases students' independence in learning mathematics during the Covid-19 pandemic.…”
Section: Significance Of the Studymentioning
confidence: 99%
“…Although some studies have shown that Flipped Classroom has a significant impact on enhancing mathematical skills, for instance, the research conducted by Albawi (2018); Ario & Asra (2018); Casem (2016); Darwani et al (2023); Khoirotunnisa & Irhadtanto (2020); Nida et al (2019); Nurfadillah (2022); Pinontoan and Walean (2019);and Zebidi (2021). However, there are also other studies that state no significant difference between the Flipped Classroom approach and the traditional approach (Andriani et al, 2022;Jarah & Diab, 2019;Ramadhani, 2019;Zineddine, 2018). The contradictions in these research findings may be attributed to moderator factors influencing the effectiveness of the Flipped Classroom method in the context of mathematics learning.…”
Section: Introductionmentioning
confidence: 99%
“…Learning media is very helpful in delivering and understanding the material. One of the learning media that helps to learn and can explore students' critical thinking abilities is Geogebra (Andriani et al, 2022;Batubara, 2019).…”
Section: Introductionmentioning
confidence: 99%